2014
DOI: 10.1186/1471-2407-14-529
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profile in very young women with breast cancer

Abstract: BackgroundBreast cancer is rarely diagnosed in very young women (35years old or younger), and it often presents with distinct clinical-pathological features related to a more aggressive phenotype and worse prognosis when diagnosed at this early age. A pending question is whether breast cancer in very young women arises from the deregulation of different underlying mechanisms, something that will make this disease an entity differentiated from breast cancer diagnosed in older patients.MethodsWe performed a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 75 publications
5
59
0
Order By: Relevance
“…It has been reported that miR-1207-5p is upregulated in CRC tissues and a wide variety of cancer tissues and cell lines [30,45,46]. Our observation that forced expression of miR-1207-5p in human colonic epithelial cells, HCoEpiC and CCD841 alters their morphology to a more elongated EMT phenotype-a marker for invasion and metastases and causes an increased expression of a number colon CSC markers which among others include CD44, CD166, and CD133 as well as Slug, Snail, and Vimentin further suggests an involvement of this miR in induction of stemnness in colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-1207-5p is upregulated in CRC tissues and a wide variety of cancer tissues and cell lines [30,45,46]. Our observation that forced expression of miR-1207-5p in human colonic epithelial cells, HCoEpiC and CCD841 alters their morphology to a more elongated EMT phenotype-a marker for invasion and metastases and causes an increased expression of a number colon CSC markers which among others include CD44, CD166, and CD133 as well as Slug, Snail, and Vimentin further suggests an involvement of this miR in induction of stemnness in colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared molecular features of BC to age and have shown that BC tumors in young women have distinct gene expression profiles and deregulated signaling pathways (Anders et al, 2008;Pirone et al, 2012;Colak et al, 2013;Peña-Chilet et al, 2014). The up-regulated miR-125a-5p in younger patients indicates that miR-125a-5p may play an important role in BC development in an age-dependent manner, although its effects and possible targets need to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, there was an increased methylation of BRCA1, BRCA2, ATM, CHEK2, MLH1, MSH2, and MSH6, while methylation in CDH1 was increased in the blood. PMS2 was hypomethylated, and PALB2 was hypermethylated in most of the tumor samples 40,43,53 . This study yielded interesting insights on specific methylation patterns in the main genes involved in BC carcinogenesis.…”
Section: Epigenetic Profile In Ywbcmentioning
confidence: 99%
“…Some experimental data suggest that there is a particular miRNA expression pattern in YWBC [40][41][42] . Peña-Chilet et al 40 studied the miRNA profile of 45 YWBC (defined as ≤35 years) compared to older women and found a unique expression of 96 miRNAs according to age (p < 0.05). The research group validated the expression of 6 miRNAs, finding upregulation of miRNA-1228*, miRNA-3196, miRNA-1275, and miRNA-1207, and downregulation of miRNA-139-5p and miRNA-92b.…”
Section: Micro-rna (Mi-rna) Expression Profiles In Ywbcmentioning
confidence: 99%
See 1 more Smart Citation